Understanding Doctoral Struggles: A Multi-Disciplinary Case Study of Methodological and Institutional Challenges - Narsimha Rao Dandala; Nduka Rapheal Ejeh; Saher Yusuf; Juliet Ukamaka Okpara; Nimisha S; Wirngo Peter Ayukea; Hellen Mukami Munyi; Abdulkarim Abdullah AlHussaini; Aida Mehrad (POPULIKA, 2026)
Doctoral students across disciplines frequently encounter methodological difficulties that can delay progress, affect research quality, and contribute to attrition; however, empirical, cross-disciplinary studies that explain why these challenges occur and how they are shaped by institutional contexts remain limited. This study explores the methodological challenges doctoral candidates face across four disciplines: Business Administration (DBA), Computer Science (DCS), Science (DSc), and Arts (DA), and examines how disciplinary norms, supervisory practices, and institutional structures shape these experiences. Using an explanatory multi-case study approach, nine doctoral candidates were purposefully selected to represent diverse disciplinary and institutional backgrounds. Data were gathered through semi-structured interviews and analysis of key research documents and were examined thematically to identify recurring patterns and contextual influences. The findings reveal both discipline-specific challenges, such as differing assumptions about knowledge and research design, and cross-cutting issues, including misaligned supervision, constraints on ethical approval, emotional strain, and limited institutional support. By comparing cases across disciplines, the study highlights how contextual factors contribute to these difficulties and, in some instances, help mitigate them. Based on these insights, the study offers practical recommendations, including clearer alignment of supervisory roles, earlier and more structured methodological and ethical training, and increased access to interdisciplinary research support. Overall, this research contributes empirical evidence to the doctoral education literature and underscores the need for systemic improvements to enhance doctoral students’ research experiences and outcomes. Keywords: Case Study; Methodology Challenges; Research Methodology.